ASSESSMENT OF PHYSIOLOGICAL AND YIELD-RELATED RESPONSES OF UPLAND COTTON (GOSSYPIUM HIRSUTUM L.) UNDER DROUGHT STRESS CONDITIONS - Matniyazova H. (Modern American Journals, 2025)
This research examined the physiological and yield responses of 18 advanced upland cotton (Gossypium hirsutum L.) lines together with the cultivar Namangan-77 under contrasting water regimes. Significant genotypic variation was detected for total water content, transpiration rate, and yield components in both optimal and drought-stressed environments. Lines L-1, L-24, and L-29 showed reduced susceptibility to water deficit based on physiological and agronomic performance, indicating their potential use in breeding for drought tolerance. Lines L-2, L-11, and L-24 produced heavier seeds under well-watered conditions, though drought markedly decreased seed weight and fiber yield in most genotypes. Overall, the study provides practical implications for developing cotton varieties with improved drought adaptation and stable yield potential.
Keywords: Upland cotton (Gossypium hirsutum L.), water regimes, drought conditions, physiological traits, chlorophyll, carotenoids, morpho-agronomic traits.